(3EOGQI GdGFJeGf (B/s - (3GQTjO, YHO GdeYWj QVGs; (3LhOI, eMahX GMeO s ((3hGFd(B: s (3OGQ hGFd(B, s, 1999)
(3GdeHGOF GdYGeI ddGFJeGf GdeUQaj , GdJfXje h GdGFJeGf GdeUQaj , OhQ JMhd GdCUhd , GdVeGfGJ h CfhGY GdJSgjdGJ GdGFJeGfjI Jbjje GdSfOGJ h GSJgdGc GdOjhf GdSfOjI , GSJHOGd GdOjhf WhjdI GdGLd , GOGQI GdGFJeGf h GdJMdjd GdeGdj h eJGHYI GdGFJeGf h CNjQG GSJgdGc GdbQhV(B.s
Keywords: (3GdGOGQIs; (3GdJSdjas; (3Hfhc GdJSdjas; (3eUGQa GdEFJeGfs